Incidence of shoulder dystocia and risk factors for recurrence in the subsequent pregnancy—A historical register‐based cohort study - Jeppegaard, Maria; Larsen, Marie H.; Thams, Amalie B.; Schmidt, Amalie B.; Rasmussen, Steen C.; Krebs, Lone (Acta obstetricia et gynecologica Scandinavica, 2024)
Introduction Shoulder dystocia is a rare obstetric complication, and the risk of recurrence is important for planning future deliveries. Material and Methods The objectives of our study were to estimate the incidence and risk factors for recurrence of shoulder dystocia and to identify women at high risk of recurrence in a subsequent vaginal delivery. The study design was a nationwide register‐based study including data from the Danish Medical Birth Registry and National Patient Register in the period 2007–2017. Nulliparous women with a singleton fetus in cephalic presentation were included for analysis of risk factors in index and subsequent delivery. Results During the study period, 6002 cases of shoulder dystocia were reported with an overall incidence among women with vaginal delivery of 1.2%. Among 222 225 nulliparous women with vaginal births, shoulder dystocia complicated 2209 (1.0%) deliveries. A subsequent birth was registered in 1106 (50.1%) of the women with shoulder dystocia in index delivery of which 837 (77.8%) delivered vaginally. Recurrence of shoulder dystocia was reported in 60 (7.2%) with a six‐fold increased risk compared with women without a prior history of shoulder dystocia (risk ratio [RR] 5.70, 95% confidence interval [CI]: 4.41 to 7.38; adjusted RR 3.06, 95% CI: 2.03 to 4.68). Low maternal height was a significant risk factor for recurrence of shoulder dystocia. In the subsequent delivery, significant risk factors for recurrence were birthweight >4000 g, positive fetal weight difference exceeding 250 g from index to subsequent delivery, stimulation with oxytocin and operative vaginal delivery. In the subsequent pregnancy following shoulder dystocia, women who underwent a planned cesarean (n = 176) were characterized by more advanced age and a higher prevalence of diabetes in the subsequent pregnancy. Furthermore, they had more often experienced operative vaginal delivery, severe perineal lacerations, and severe neonatal complications at the index delivery. Conclusions The incidence of shoulder dystocia among nulliparous women with vaginal delivery was 1.0% with a 7.2% risk of recurrence in a population where about 50% had a subsequent birth and of these 78% had subsequent vaginal delivery. Important risk factors for recurrence were low maternal height, increase of birthweight ≥250 g from index to subsequent delivery and operative vaginal delivery. The risk of recurrent shoulder dystocia in a subsequent vaginal delivery is 7%. Maternal height, positive fetal weight difference >250 g between the index and subsequent delivery, high fetal weight and operative vaginal delivery are identified as significant risk factor.